Pengetahuan dan paparan media berhubungan dengan perilaku remaja dalam membaca label informasi nilai gizi - Khairinisa, Sari; Hidayanti, Lilik; Susilowati, Prima Endang (Nutrition Scientific Journal, 2024)
The consumption pattern of the community, including adolescents, has shifted to consuming ready-to-eat or packaged foods. This phenomenon needs to be controlled because these foods are generally high in sugar, salt and fat which are bad for health. This habit can arise partly due to low compliance to read nutritional value information labels. This study aims to analyze the factors associated with adolescent behavior in reading nutritional value information labels. The research method used cross sectional design with proportional stratified random sampling. The research sample was SMAN 1 Singaparna students, with a total of 328 people. Data were collected using a questionnaire instrument and analyzed by Chi Square Test. The results showed that there was a relationship between knowledge and the behavior of reading nutritional value information labels (p value = 0.009; OR = 1.859; 95% CI = 1.190-2.903) Media exposure also had a relationship with the behavior of reading nutritional value information labels (p value = 0.000; OR = 6.128; 95% CI = 2.857-13.137). However, there was no relationship between attitude (p value = 0.376), ability to read labels (p value = 0.264), special diet (p value = 0.130), gender (p value = 0.357) and pocket money (p value = 0.434) with the behavior of reading nutritional value information labels. Based on the results of this study, it can be concluded that knowledge and media exposure affect the behavior of reading nutritional value information labels, as well as being a risk factor. Therefore, it is recommended that students make it a habit to read nutrition labels before choosing packaged food products.